Effectiveness of Mindfulness-Based Stress Reduction (MBSR) in Managing Hypertension among Adults in Indonesia - Anggraini , Dewi (International Journal of Health Sciences, 2025)
Purpose: The aim of the study was to investigate the effectiveness of mindfulness-based stress reduction (MBSR) in managing hypertension among adults Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Mindfulness-based stress reduction (MBSR) effectively reduces blood pressure by managing stress and enhancing relaxation. Studies show significant reductions in systolic and diastolic pressure, particularly in individuals with resistant hypertension. MBSR programs are most beneficial when tailored to cultural contexts and when participants maintain consistent practice. It serves as a valuable, non-pharmacological complement to traditional hypertension treatments, improving overall well-being and long-term health outcomes. Unique Contribution to Theory, Practice and Policy: Biofeedback theory, cognitive behavioral theory (CBT) & transactional model of stress and coping may be used to anchor future studies on the effectiveness of mindfulness-based stress reduction (MBSR) in managing hypertension among adults. It emphasizes the importance of addressing both mental and physical health, providing a complementary treatment to traditional medical interventions such as medication. As a non-drug treatment, MBSR can reduce reliance on expensive medications, offering a more affordable alternative for long-term hypertension management.